Guayaramerim: a borderland marked by the Mamore River and its “cachuelas” - Bianca De Marchi-Moyano; Laura Helena Arraya-Pareja (Íconos)
This article uses the case of the Bolivian frontier city of Guayaramerin- located in that country´s Beni Department- as a springboard for a discussion of the relationship between water courses and national borderlines. This urban settlement is located on the shores of the important Amazonian Mamoré River and is placed just across an almost homonymous Brazilian city: Guajará-Mirim. The article describes the site where the city was built, its historical permanency, and the role played by the river and its cascades in encouraging its founding just on the borders between Bolivia and Brazil. Gathering information over a specific locale and not about a line or a political/administrative area is prioritized. Thus, the chosen methodology consists in focusing on, and contrasting historic, legiasltive and sociological documents dealing with the selected location, in an effort to understand its establishment, development and durability in a border setting. Also, the colonial past is examined, together with early exploration efforts of the region under the republic and the sources of place names and of population dynamics. Additionally, the diplomatic processes which defined the border during the rubber era, are investigated. Finally, a sketch of recent history is provided in an effort to identify new trends in the trade flows and population exchanges that are taking place in situ. The article ends with a discussion of its own potential contributions to current debates about the Amazonian frontier.